Assessing distress tolerance using a modified version of the Emotional Image Tolerance task. Issue 2 (30th April 2021) - Slabbert, Ashley; Hasking, Penelope; Notebaert, Lies; Boyes, Mark
The Emotional Image Tolerance (EIT) task assesses tolerance of negative emotion induced by negatively valenced images. We made several minor modifications to the task (Study 1) and adapted the task to include positive and neutral images in order to assess whether individuals respond to the valence or the intensity of the image content (Study 2). In both studies, we assessed subjective distress, gender differences in task responses, and associations between behavioral and self-reported distress tolerance, and related constructs. Across both studies, the EIT successfully induced distress and gender differences were observed, with females generally indicating more distress than males. In Study 2, responses on the adapted EIT task were correlated with self-reported distress tolerance, rumination, and emotion reactivity. The EIT successfully induces distress and the correlations in Study 2 provide promising evidence of validity.